ORGANIZATIONAL COMMITMENT OF HEALTHCARE EMPLOYEES IN A PRIVATE SECTOR - Dugalic, Stefan; Santric- Milicevic, Milena; Stanisavljevic, Dejana; Gutic Vukobrat , Bojana; Gojnic, Miroslava; Macura, Maja; Bozic, Dragana; Stanisavljevic, Tamara; Petronijevic, Milos; Vrzic- Petronijevic, Svetlana; Petronijevic, Milica; Todorovic, Jovana (Medical Research, 2022)
Introduction: Organizational commitment is defined as ‘psychological relationship of an individual with an organization’. The aims of this study were to analyze organizational affective and normative commitment of young healthcare providers, factors that determine their perception of organizational support, as well as to identify possibilities to promote employee dedication to the healthcare organization they worked for. Method: The research was conducted as a cross-sectional study in a private healthcare institution ‘Fizio Vracar’ in Belgrade. Meyer-Allen questionnaire (with 24 questions) was distributed during the third week of May 2018, and 30 physical therapists of both sexes and with median age 29.9 completed it, voluntarily and anonymously. Results: The hypothesis was proven: organizational normative commitment declined with the increase of organizational support (r=-0.526; p<0.001), while organizational affective commitment increased with the increase of organizational support (r=0.756; p<0.001). On the scale from 1 to 5, all the employees had the average score above 3 for affective and normative commitment (3.72±0.56 and 3.19±0.75), while the score for organizational support was above 4 (4.11±0.54). The model of multiple linear regression showed that affective and normative commitment were factors that determined the perception of organizational support (B=0.66; 95% CI: 0.41-0.91; and B=-0.20; 95% CI: -0.38; -0.02). Conclusion: Even though organizational support had better score than affective and normative commitment, there is certainly room for their improvement. Managers and employees should consider the employee requests together, care more about employee general satisfaction, empower team spirit, while the organization should implement mechanisms to retain work force.